Paratextos del arte contemporáneo 2. Los espacios del arte - Proyecto - Moyinedo, Sergio (2015)
This is the second stage of the project “Paratexts of the contemporary art” developed during 2013/14. In this stage we propose a field work at two artistic institutions since the analysis of a serie of temporary exhibitions. The aim of this phase is analyse the contemporary work of art in some of its privileged location, realizing how in every case, the paratextual system –formed by architectural space, website, signs and labels, etc.- determines the contemporary circulation of the work of art.